Der Syndikus-Steuerberater Zum Spannungsfeld zwischen freiem Beruf und angestellter Tätigkeit - Niemann, Helen (Universitätsverlag Göttingen, 2020)
The liberal professions are subject to an ever changing legal basis and thus constantly undergo minor or major amendments. A fundamental innovation in the current law governing the liberal professions of tax consultants is the authorization to work as in-house tax consultants. Since 2008, the Tax Consultancy Act has made possible to pursue the profession of in-house tax advisor, while lawyers were allowed to work in-house for decades already, with the last amendment of the legal regulations from 2016. This paper deals with the various legal and practical implications of the interactions between the freelance activity as a tax consultant and the activity of in-house tax consultants in an employment relationship. A detailed comparison of the legal basis for tax consultants with that of in-house lawyers is of special interest in light of the current ambiguous legal situation. Special focus is a thorough analysis of the legal question whether or not an in-house tax adviser can be exempted from the obligatory pension insurance.